Postintubacná stenóza trachey--nase skúsenosti - Belák, J; Janík, M; Vajó, J; Sauka, C; Kudlác, M; Frigová, L; Zák, V; Michlík, J (Rozhledy v chirurgii, 2006)
Stenoses of the respiratory tract are life threatening conditions of various origins. The authors give referrence on 21 patients operated for postintubation stenoses of their trachea at the IInd Surgical Clinic of the UPJS Medical Faculty, the Faculty Hospital of L. Pasteur in Kosice, from 01. 01. 1999 to 30. 06. 2005. All patients had a tracheobronchoscopic examination and a CT examination completed prior to the procedure. Within 24 hours of their admission, 9 patients were operated, 7 underwent resection procedures and 2 patients had Montgomery's T-cannula introduced. 12 patients had their procedures planned, and were operated later than 24 hours after their admission. 10 patients underwent resections of the trachea, 2 had Montgomery's T-cannula implanted. The postoperative course following the resection of the trachea was without complications in 14 patients, 1 patient experienced transitional oedema in the anastomosis and 2 patients suffered restenoses. In this patient group, no fatal case was recorded. The authors stress up multidisciplinary approach in the diagnostics and treatment of the postintubation stenoses of trachea. In cases of postintubation stenoses of trachea, resection of the trachea with primary anastomosis represents the most advantageous treatment approach for the patient.
Keywords: Tracheal Stenosis; Tracheostomy; dospělí; Humans; Intubation, Intratracheal; Adult; intratracheální intubace; tracheostomie; Child; dítě; lidé; stenóza průdušnice